Tra esperienza vissuta e tonalità emotiva. L’affettività nella riflessione heideggeriana su natura e tecnica - Bisceglia, Aldo (Bollettino Filosofico, 2023)
This essay offers a new reading of the relationship between nature and technology in Heidegger’s post-Turn writings, starting from the question of affectivity. The emphasis will be on writings from the 1930s to the 1960s, when an in-depth investigation into the question of Stimmung and the role played by Grundstimmungen became increasingly relevant within the context of the thinking of Event. The purpose of this essay is twofold: it aims to show that for Heidegger mood ultimately always determines both the human-technology and the human-nature relationship; also, it attempts to show that disposedness, in its authentic version (Stimmung), as in its inauthentic one (Erlebnis), plays a decisive role in redefining the capabilities and limits of the technological man in their relationship with nature. Keywords: Affectivity, Heidegger, Measure, Nature, Technology